Understanding the Primary Care Experience in a Student-Run Free Clinic - Kamal, Salmaan; Hoge, April; DeRussy, Aerin; Austin, Erika; Pollio, David; Montgomery, Ann Elizabeth; Kertesz, Stefan (Journal of Student-Run Clinics, 2023)
Background: Over 100 student-run free clinics (SRFCs) operate in the United States (US), typically serving uninsured populations. To date, there has been no effort to compare the patient-reported primary care experience in SRFCs to those of mainstream primary care (PC) clinics serving similar populations. In this study, we surveyed patients at Equal Access Birmingham (EAB), an SRFC, and compared our results to those from two PC clinics serving homeless-experienced clientele. Methods: We surveyed 60 EAB patients with the validated “Primary Care Quality-Homeless” survey. It generates an overall score and 4 subscale scores (clinician-patient Relationship, perceived inter-provider Cooperation, Accessibility/Coordination, Homeless-Specific Needs). We compared EAB’s ratings to those published for a Veterans Affairs (VA) mainstream PC (n=150) clinic and a homeless-tailored non-VA Health Care for the Homeless (HCH) program (n=195). Results: EAB’s ratings were similar to those of the mainstream VA clinic (p>0.4). EAB scored lower than the homeless-tailored non-VA HCH program in each subscale, though the difference did not achieve statistical significance. EAB patients most often praised the staff’s interpersonal skills. Items in which >25% of respondents gave a negative rating concerned wait times (29%), coordination of care (65%), and perceptions of provider skill (43%). Conclusions: Despite constrained resources, an SRFC scored comparably to a mainstream VA PC setting. SRFCs will play a continuing role in care of uninsured individuals, and while these data suggest SRFC patient experiences are mostly favorable, additional resources may be required to approximate the care experience achieved in clinics tailored for homeless persons.